Kepercayaan Dinamisme Masyarakat Postkolonial Jawa dalam Novel Entrok Karya Okky Madasari - Fitri Nurul Afni (STKIP PGRI Jombang, 2020)
The diversity of beliefs in Javanese dynamism is the object of cultural reflection in postcolonial societies in the novel Entrok by Okky Madasari. The beliefs of the postcolonial Javanese community were dominant with Javanese traditions handed down by ancestors and the results of acculturation that formed the compilation of the colonial period. The purpose of this article is the conversion of Javanese post-colonial beliefs in Entrok's novel that reflects Javanese traditions handed down by ancestors or the results of acculturation that formed the compilation of the colonial period. This article uses descriptive methods using qualitative methods, using literature study techniques, and data analysis in the form of data reduction, data presentation, and making conclusions. This article contains the dynamism beliefs about belief in Kawi Mount, sacred trees, tuyul, and witchcraft.